Issues of Cluster Formation in East Germany - N. A. Ermakova; L. A. Karimova (Управленческое консультирование)
The article is devoted to modern innovation policy in Germany. The German government considers stimulation of cluster structures as a necessary condition for achieving high-tech development of the country, so the cluster policy is a component of German innovation policy. The article considers the concept of three-level organization of clusters, quantifies the value of regional asymmetry in investment in innovation. Based on the classification of clusters by M. Porter, using the methodology of the analysis of cluster sectors of the European Cluster Observatory, the author’s method of the substantive typologization of clusters by L. Markov and the model of organizational development proposed by D. Napolskikh, the identification of East German clusters was conducted, the clusters most significant for economic development of the East German states were identified. Their brief characteristics were presented and the degree of maturity was determined. The results of the research conducted by the authors of the article and the report of European experts Franco, S., Wilson, J., concerning Saxony’s clusters were compared, and recommendations on conducting cluster policy in structurally weak regions were given. The author’s maps illustrating the results of the study are included in the article.